Pendampingan Masyarakat sebagai Deteksi Dini Konflik Sosial dalam Penguatan Moderasi Beragama di Kabupaten Tulungagung - Naibin Naibin; Maftukhin Maftukhin; Amrullah Ali Moebin; Edi Nurhidin; Ahmad Fahrudin (Community: Jurnal Pengabdian Kepada Masyarakat, 2023)
This paper is to photograph diversity in the dimensions of conflict that occur in the Tulungagung community. The purpose of this paper is to provide community assistance as an early detection of social conflict in strengthening religious moderation in Tulungagung district. The approach used in this study is the ABCD (Asset-based Community Development) service method which aims to identify and utilize the potential and resources owned by local communities in reducing potential social conflicts that can arise due to differences in religious beliefs. The results of this community service found that it was important for the religious instructor (penyuluh agama) to understand the map of social conflicts to help them resolve these conflicts.